MONEY OR SOVEREIGNTY: THE IMPACT OF CHINESE FOREIGN DIRECT INVESTMENT ON CAMBODIA - Millenia Pani, Gema (Kajian Asia Pasifik, 2024)
This paper examines the implications of China's massive foreign direct investment (FDI) in Cambodia through the lens of Dependency Theory. Drawing on the theoretical perspectives of Theotonio Dos Santos and Fernando Henrique Cardoso, this study analyses how China's capital hegemony and foreign financing have led to Cambodia's dependence on Chinese investment. The findings reveal that the influx of Chinese FDI, while contributing to economic growth and infrastructure development, has also resulted in negative consequences across political, socio-cultural, environmental, and socio-economic dimensions. The dominance of Chinese investment has undermined Cambodia's governance, eroded local autonomy, exacerbated corruption, marginalized local communities, and caused environmental degradation. This study argues that Cambodia's reliance on foreign capital, compounded with inadequate governance, has perpetuated its dependency on China, compromising its sustainable development and national interests. This study emphasizes the importance for Cambodia to reduce its dependence on foreign investment, strengthen domestic economic capacity, and prioritize national interests through sound governance and regulatory mechanisms to mitigate the negative impacts of FDI.